DETERMINANT FACTORS OF THE SUSTAINABILITYOF BARN GROUP (Case in â€œKarya Taniâ€ Barn Group, Pasir Malati Village, Dawuan Sub district, Majalengka Regency, West Java Province, Indonesia) - Jaka Sulaksana; Merida Dwiprani Rahayu (Paradigma Agribisnis, 2018)
This paper describesBarn Group sustainability (its level and factors affecting on it)and find the model that can keep this group survive. This research was conducted in the the Pasirmalati Village, Dawuan Subdistrict,Majalengka regency with the method ofÂ  census to 45 farmers.Â  The results showed that group sustainability level components (includes service attitude, system of borrowing, lending terms, the accuracy of the service and the overall amount of loans)in range of average to very good level. Land ownership, formal education, informal education, the attitude of members toward theBarn Group, and the attitude of members toward the leadership of group jointly affect the level of group sustainability. Land area, formal education, informal education, and the attitude of members to the leadership of group independently does not affect the level of group sustainability. However, the attitude of members to the Barn Group independentlyhas an effect on it.